EFEKTIFITAS BERBAGAI MULSA DAN KETEBALAN DALAM MENEKAN PERTUMBUHAN GULMA TEKI-TEKIAN (Chyperus rotundus L.) PADA BUDIDAYA BAWANG MERAH (Allium cepa L.) - Lentina Sitinjak; Juli Lousiana Butar-butar (JURNAL AGROTEKNOSAINS, 2021)
Chyperus rotundus L. is a weed that is very fast spreading, growing and developing. Nut weeds can have a high adaptability seen from the ability to grow in various types of land. Starting from dry land, humid land to wet / inundated or muddy land. Sandy, clay or sandy loam land. This nut weed also has a high competitive power in terms of its ability to compete with other weeds, to keep growing and tends to be the dominant weed in a planted area. Various attempts were made to suppress the growth of this weed nut. Mulch is a method used to suppress the growth of nut weeds in this study. There are three types of mulch used in this study, namely rice husks, rice straw and reeds and control treatment. The three mulches were applied to two thicknesses, namely the thickness of 250 gr / plot and 500 gr / plot. The results showed that the inorganik mulch treatment of rice husks, straw and alang alang and its thickness of 250 g / m² and 500 g / m² did not have a significant effect in suppressing the growth of nut weed (Chyperus rotundus L.). Straw mulch first undergoes decomposition compared to rice husk mulch and Imperata, so that the percentage of growth of shallot (allium cepa L.) plants is higher than with submerged mulch and reeds.